Successful living donor liver transplantation of the left lateral sector with simultaneous atypical resection of the S2 for focal nodular hyperplasia - R. T. Rzayev; Yu. R. Kamalov; E. Yu. Kryzhanovskaya; M. A. Tatarkina; A. L. Kovaleva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The purpose of presenting a clinical observation. Description of a clinical observation of a successful atypical resection of focal nodular hyperplasia of the segment II of the liver to a relative donor, followed by transplantation of the left lateral sector of the liver to a one-year-old child with cirrhosis of the liver in the outcome of biliary atresia.General provisions. Patient Z., 29 years old, was examined as donor for related liver sector transplantation. The oval structure with fairly smooth contours, hyperechoic in the central parts and hypoechoic in the periphery, was found in the segment II during the ultrasound examination; assessment of blood flow was difficult due to acoustic interference. According to computed tomography, it was a weak hypervascular formation with fuzzy contours, accumulating contrast medium unevenly in the arterial phase, with visualization of a small hypodense area around, also accumulating contrast medium in the venous phase. According to magnetic resonance imaging, there is a zone of increased MR signal, with contrast enhancement uniformly accumulating contrast in the arterial phase. It was assumed that the patient had focal nodular liver hyperplasia. The patient underwent surgery, during which the left lateral sector of the liver was removed and a single-step atypical resection of the segment II was performed. Histological examination of the surgical material confirmed the presence of FNH. After excision and suturing of vascular structures in conditions of continued blood circulation, the left lateral sector was removed from the wound and implanted into the recipient in an orthotopic position. The postoperative period passed without complications. The donor and recipient were discharged from the hospital in a satisfactory condition on the planned date.Conclusion. This observation demonstrates the possibility of using a liver fragment as a transplant after resection of focal nodular hyperplasia.